The Relationship Of Learning Patterns Between The Independent Learning Curriculum, Deep Learning, And The Concept Of Integration-Interconnection And How The Position Of Islamic Education - Saputra, Nahrul; Abdullah, Mudhofir; Yahya, Ismail (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This research aims to describe and explore the relationship between the independent curriculum, the concept of deep learning, and the concept of integration-interconnection. In this research, the approach used is qualitative-descriptive and literature-based analysis. This type of research is library research, while the analysis used is content analysis. The results of this study show that the relationship between the independent curriculum, deep learning, and the concept of integration-interconnection is a complementary relationship. The presence of the concept of deep learning is a further development of the independent curriculum, while the concept of integration-interconnection is present as an effort to bring together scientific disciplines, especially Islamic sciences and general sciences that were previously dichotomised. The emergence of the deep learning concept does not necessarily negate the role and contribution previously made by the independent curriculum, but as checks and balances, while the concept of integration-interconnection emphasizes the importance of greeting each other between scientific disciplines, dialogue, or even integration between scientific disciplines. The learning pattern of the independent curriculum emphasises students’ liberties to develop their talents, interests and creativity. Deep learning emphasises the depth and meaningfulness of students’ understanding. Meanwhile, the concept of integration-interconnection emerges as an effort to provide a productive relationship between scientific disciplines, rather than a negating relationship. In the independent curriculum, there are several key concepts in its implementation, such as project-based learning, problem-based learning, inquiry-based learning, discovery learning, discussion learning, cooperative learning, and differentiated learning. While in the concept of deep learning, such as meaningful learning, mindful learning, and joyful learning. While the concept of integration-interconnection, such as lesson content, renewal of methods and religious lectures, and reconstruction of materials, methods, and approaches. Islamic education offers the concept that in addition to strengthening the learning aspects of worldly dimensions such as skills in work, but also on aspects of faith, morals, and other relevant matters.